PENGARUH BODY SHAMING TERHADAP TINGKAT KEPERCYAN DIRI PADA MAHASISWA - Aliyah Tri Hastari; Ardi Wiyatno; Mardhilla Farhana; Reza Juliantini; Salsa Jeni Nabilla Syamsul; Serli Saputri (CV. Doki Course and Training, 2023)
Individuals who experience body shaming, in the form of negative words to demean someone that lead to physical appearance, such as body shape, face, skin color and so on. Thus creating a sense of lack of confidence in individuals who find body shaming. The purpose of this study was to determine the relationship of body shaming to the level of self-confidence in students of Raden Fatah State Islamic University Palembang. The study used quantitative data with a cross sectional approach, by distributing questionnaires using convenience sampling techniques in sampling, with a sample of 101 respondents. As many as 69% of respondents experienced moderate category body shaming. As many as 58% of respondents experienced moderate category confidence. There is a correlation between body shaming and self-confidence in students.